Pemanfaatan Limbah Serbuk Kayu dalam Pembuatan Wood Pellet untuk Efisiensi Pengolahan Produk Pakan Ternak: Utilization of Sawdust Waste in the Manufacture of Wood Pellets for Processing Efficiency of Animal Feed Products - Tyas Lilia Wardani; Amalia Diah Artanti; Widyarsi Nur Hamidah; Tutug Bolet Atmojo; Ratna Fajariani; Isna Qadrijati; Seviana Rinawati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The Sumber Urip Rabbit Breeders Association has a role in the economic development of Karanganyar Regency. It is necessary to empower rabbit breeders, including maintaining the supply of fuel for the processing of rabbit feed, namely hay grass. Rabbit farmers in the village of Padon Gayamdompo Karanganyar are currently using LPG as fuel for processing hay grass. Still, the erratic availability of LPG and the relatively high cost of purchasing LPG are obstacles. Wood pellets are an alternative fuel source that rabbit breeders can use in Karanganyar Regency. There is a sawmill near the rabbit breeders' association, which produces a large amount of unused sawdust. The solution offered to the Sumber Urip Rabbit Breeders Association is alternative energy from wood pellets. The Community Partnership Program (PKM) is implemented by socializing wood pellets, making wood pellet machines and their furnaces, practicing making wood pellets while testing wood pellet machines, practicing using wood pellet stoves for hay grass processing, and calculating the efficiency of fuel use wood pellets in hay grass processing. The impact of this PKM activity is that rabbit breeders gain knowledge and skills in making wood pellets, using them as fuel, and benefiting from using wood pellets, reducing the cost of processing hay grass by 33%.